To the end of the earth : a history of the crypto-Jews of New Mexico - Hordes, Stanley M. (Columbia University Press, 2005)
Stanley M. Hordes explores the remarkable story of crypto-Jews and the tenuous preservation of Jewish rituals and traditions in Mexico and New Mexico over the past five hundred years. He follows the crypto-Jews from their origins in medieval Spain and Portugal to their efforts to escape persecution by migrating to the New World and settling in the far reaches of the northern Mexican frontier. Drawing on individual biographies, family histories, Inquisition records, letters, and other primary sources, Hordes provides a richly detailed account of the economic, social, and religious lives of cryp.